SARS-CoV-2 infection in mortuary and cemetery workers. (April 2021) - Alishaq, Moza; Jeremijenko, Andrew; Nafady-Hego, Hanaa; Al Ajmi, Jameela Ali; Elgendy, Mohamed; Fadel, Rayyan Abdulaziz Attya; Thomas, Anil George; Alahmed, Mohammed A.A.; Ammar, Adham; Bensaad, Meryem; Al-Barghouthi, Bayan; Coyle, Peter; et al.
Highlights: A substantial proportion of mortuary and cemetery workers in Qatar have serologic evidence of SARS-CoV-2 infection (19.1% and 29.6% respectively). Factors associated with infection were symptoms in the preceding 2 weeks, younger age and contact with a known case. Our data are most consistent with community-acquisition rather than occupational-acquisition. Abstract: Background: Mortuary and cemetery workers may be exposed to the bodies of people with SARS-CoV-2 infection; however, prevalence of infection among these groups is unknown. Methods: Nasopharyngeal swabs (NPS) for RT-PCR and serologic testing for SARS-CoV-2 were performed on mortuary and cemetery workers in Qatar. Data on specific job duties, living conditions, contact history, and clinical course were gathered. Environmental sampling was carried out to explore any association with infection. Logistic regression analysis was used to determine the factors associated with infection. Results: Forty-seven mortuary workers provided an NPS and seven (14.9%) were PCR positive; 32 provided a blood sample and eight (25%) were antibody positive, six (75%) who were seropositive were also PCR positive. Among the 81 cemetery workers, 76 provided an NPS and five (6.6%) were PCR positive; 64 provided a blood sample and 22 (34.4%) were antibody positive, three (13.6%) who were seropositive were also PCR positive. Three (22.2%) and 20 (83.3%) of the infected mortuary and cemetery workers were asymptomatic, respectively. Age <30 years (OR 4.9, 95% CI 1.7–14.6), community exposure with a known case (OR 4.7, 95% CI 1.7–13.3), and presence of symptoms in the preceding 2 weeks (OR 9.0, 95% CI 1.9–42.0) were independently associated with an increased risk of infection (PCR or antibody positive). Of the 46 environmental and surface samples, all were negative or had a Ct value of >35. Conclusion: A substantial proportion of mortuary and cemetery workers had evidence of SARS-CoV-2 infection, which was incidentally detected upon serologic testing. These data are most consistent with community acquisition rather than occupational acquisition.